In vitro Free Radical Scavenging Activity of Ethanolic Extract of Cucumis trigonus Roxburxii fruit - Balakrishnan, A (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTCucumis trigonus Roxburghii of family Curcurbitaceae is a perennial scabrid monoecious tendrillar herb commonly used in Indian folklore medicine. The present study investigates the antioxidant potential of ethanolic extract of the fruits of Cucumis trigonus. They were investigated for 1, 1-diphenyl-2-picrylhydrazyl (DPPH) free radical, Superoxide radical, Nitric oxide radical, hydroxyl radical scavenging activity and reducing power assay. The extract showed strong antioxidant capabilities, which were subjected for their dose dependent activity at different concentration to calculate IC50 values. Key words: Antioxidant, Cucumis trigonus, DPPH free radical, Superoxide radical and reducing power assay